S-45-1: ONCO-HYPERTENSION: CONCEPT AND FUTURE PERSPECTIVES. (January 2023) - Kidoguchi, Satoshi
Abstract : In these decades, the morbidity of cancer has been increasing worldwide. On the other hand, the development of cancer treatment, such as small-molecule inhibitors, had improved the prognosis of patients with cancer. Consequently, cardiovascular diseases in cancer-survivors have become a matter of global concern. As a matter of fact, the mortality from cardiovascular events surpasses the mortality from cancers themselves in several types of cancer. Hypertension is reported to be the most frequent comorbidity and a significant risk factor for cardiovascular diseases among cancer-survivors. Besides, many types of newly discovered small-molecule inhibitors, including vascular endothelial growth factor signaling pathway inhibitors, proteasome inhibitors and Bruton-type tyrosine kinase inhibitors have been reported to be associated with blood pressure elevation. On the other hand, there have been reports that hypertension itself is associated with the occurrence of certain types of cancer, such as kidney or colon cancer, and some researchers have raised the possibility that antihypertensive drugs, such as thiazide diuretics, could elevate the risk of skin cancer from cancer registry database. From these, there is a close relationship between hypertension and cancers. However, many issues have remained to be solved regarding this field. For example, few guidelines mentioned the optimal target blood pressure and appropriate types of antihypertensive drugs during and after cancer therapy. Indeed, cancer patients are excluded from major large-scale trials evaluating the effects of antihypertensive drugs, and the patients with cardiovascular diseases are excluded from trials studying the effect of anticancer therapy, which makes it difficult to draw a definite conclusion regarding these issues. Additionally, it has not been clarified whether hypertension itself or the use of antihypertensive drugs are real risk factors for certain types of cancer and the screening for cancer occurrence is necessary for patients with hypertension or antihypertensive drugs. From these, we have been proposed a new concept, Onco-Hypertension, to better understand the complex association between hypertension and cancer. The concept, Onco-Hypertension, not only covers experimental and clinical studies exploring the bidirectional association between hypertension and cancer but also pursues comprehensive management of hypertensive cancer patients to improve their prognosis and quality of life. We think that multidisciplinary team approach including experts in hypertension, oncology, cardiology, nursing and so on, is necessary to clarify the unsolved issues regarding this, Onco-Hypertension, field.